Macaronesia as a Fruitful Arena for Ecology, Evolution, and Conservation Biology - Florencio, Margarita; Patiño, Jairo; Nogué, Sandra; Traveset, Anna; Borges, Paulo A. V.; Schaefer, Hanno; Amorim, Isabel R.; Arnedo, Miquel; Ávila, Sérgio P.; Cardoso, Pedro; de Nascimento, Lea; Fernández-Palacios, José María; et al. (Frontiers in Ecology and Evolution, 2021)
Research in Macaronesia has led to substantial advances in ecology, evolution and conservation biology. We review the scientific developments achieved in this region, and outline promising research avenues enhancing conservation. Some of these discoveries indicate that the Macaronesian flora and fauna is composed of rather young lineages, not Tertiary relicts, predominantly of European origin. Macaronesia also seems to be an important source region for back-colonization of continental fringe regions on both sides of the Atlantic. This group of archipelagos (Azores, Madeira, Selvagens, Canary Islands, and Cabo Verde) has been crucial to learn about the particularities of macroecological patterns and interaction networks on islands, providing evidence for the development of the General Dynamic Model of oceanic island biogeography and subsequent updates. However, in addition to exceptionally high richness of endemic species, Macaronesia is also home to a growing number of threatened species, along with invasive alien plants and animals. Several innovative conservation and management actions are in place to protect its biodiversity from these and other drivers of global change. The Macaronesian Islands are a well-suited field of study for island ecology and evolution research, mostly due to its special geological layout with 40 islands grouped within five archipelagos differing in geological age, climate and isolation. A large amount of data is now available for several groups of organisms on and around many of these islands. However, continued efforts should be made towards compiling new information on their biodiversity, to pursue various fruitful research avenues and develop appropriate conservation management tools.